Pengaruh Konten Instagram @PSSI terhadap Pemenuhan Kebutuhan Informasi dan Kepuasan Followers - Akbar Faturrama Firgiawan; Akyas Dzakir Akrom; Trimanah Trimanah (INDO PUBLISHING, 2026)
This study examines the influence of Instagram content from @pssi on followers' information needs fulfillment and satisfaction. The Instagram account @pssi, as the official communication medium of the Football Association of Indonesia (PSSI), plays an important role in delivering information related to national football. However, a large number of followers does not necessarily indicate that information needs are fulfilled. This research employed a quantitative approach using purposive sampling with 100 active followers as respondents. Data were collected through a Likert-scale questionnaire, then analyzed using validity tests, reliability tests, normality tests, simple linear regression, t-tests, and coefficient of determination. Results indicate that Instagram content from @pssi has a positive and significant influence on both followers' information needs fulfillment (R²=0.486, t=9.631, p<0.001) and followers' satisfaction (R²=0.429, t=8.582, p<0.001). Informative, consistent, interactive, and emotionally engaging content fulfills cognitive, affective, social integration, and entertainment needs.